Urban development in Asia : pathways, opportunities and challenges - Zhang, Qian; Deng, Xiangzheng (SpringerBriefs in geography., 2017)
This book aims to present implications for China?s urban development through international comparison of urbanization process from the perspective of spatio-temporal pattern, driving factors, rural-urban interactions, development trends and economic-ecological-social synergic development. Followed the research hotspot of the international urban studies, this book identifies challenges and opportunities in the process of urban development through analyzing and comparing urbanization pathways of several Asian countries as for representatives. It provides both decision support for China?s urban development and management, and scientific support for the sustainable urban development in Asian countries.